2014
DOI: 10.1021/ci500190p
|View full text |Cite
|
Sign up to set email alerts
|

Using Information from Historical High-Throughput Screens to Predict Active Compounds

Abstract: Modern high-throughput screening (HTS) is a well-established approach for hit finding in drug discovery that is routinely employed in the pharmaceutical industry to screen more than a million compounds within a few weeks. However, as the industry shifts to more disease-relevant but more complex phenotypic screens, the focus has moved to piloting smaller but smarter chemically/biologically diverse subsets followed by an expansion around hit compounds. One standard method for doing this is to train a machine-lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 28 publications
2
101
0
1
Order By: Relevance
“…In a similar vein, as before (O'Hagan and Kell, 2015b,c; O'Hagan et al, 2015), we used the KNIME software (see http://knime.org/ and e.g., Berthold et al, 2008; Mazanetz et al, 2012; Beisken et al, 2013) to create workflows for our analyses. In particular, substantial use was made of the RDKit nodes (see http://rdkit.org/ and e.g., Landrum et al, 2011; Landrum and Stiefl, 2012; Riniker and Landrum, 2013; Riniker et al, 2013, 2014; O'Hagan and Kell, 2015b), noting the very useful “fraggle” (http://www.rdkit.org/Python_Docs/rdkit.Chem.Fraggle-module.html). The Tv similarity calculations were obtained using a node from the Indigo library (see Saubern et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…In a similar vein, as before (O'Hagan and Kell, 2015b,c; O'Hagan et al, 2015), we used the KNIME software (see http://knime.org/ and e.g., Berthold et al, 2008; Mazanetz et al, 2012; Beisken et al, 2013) to create workflows for our analyses. In particular, substantial use was made of the RDKit nodes (see http://rdkit.org/ and e.g., Landrum et al, 2011; Landrum and Stiefl, 2012; Riniker and Landrum, 2013; Riniker et al, 2013, 2014; O'Hagan and Kell, 2015b), noting the very useful “fraggle” (http://www.rdkit.org/Python_Docs/rdkit.Chem.Fraggle-module.html). The Tv similarity calculations were obtained using a node from the Indigo library (see Saubern et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Quite new is the inverse approach-to create ligand bioactivity fingerprints encoding the hit status of compounds from HTS campaigns [19,20]. In combination with conventional ligand fingerprints those allow to identify chemically similar ligands that should have similar bioactivity profiles.…”
Section: Chemical Informatics Issn 2470-6973mentioning
confidence: 99%
“…With this knowledge, we can recursively add more compounds from those families to our initial library, as we know those families may contain certain important features. This method of expanding compound libraries around the hit compounds is becoming more prevalent in the pharmaceutical industry [24]. …”
Section: 7 Stage Iv: Topological Data Analysismentioning
confidence: 99%
“…For example, prior research has shown that a machine-learning model trained on HTS and chemical fingerprints performed similar or better than a model trained on either subset alone [24]. But even such approaches suffer from the same problem of selectively favoring compounds that perform well in the tested assays.…”
Section: 8 Conclusionmentioning
confidence: 99%